Labour Relations Practices in Sugar Industry of Uttar Pradesh - Khan, Nawab Ali; Islam, Qamrul (Prabandhan: Indian Journal of Management, 2010)
Sugar industry is the most important industry in Uttar Pradesh as elsewhere in the country. The last few decades have witnessed a salient industrial revolution in this part of the country resulting in the transformation of a predominantly agricultural economy into an important industrial economy. Impressive progress has been made in the field of large, medium and small-scale industries in Uttar Pradesh. The state continues to maintain a matching position among the industrialized states of the country. There were only 14 sugar factories in Uttar Pradesh in 1932. At present, there are nearly 130 sugar mills in the state, each depending upon 150 to 400 villages for its cane supply. On an average, the industry covers about 20,800 villages. But in recent years, due to low productivity, most of the sugar mills of the state are running in losses and are unable to maintain harmonious labour relations. It is against this backdrop that the present research paper attempts to evaluate the labour management relations practices in Sugar Industry of Uttar Pradesh.